The Development of Hadhari Environmental Attitude Test Instrument for Malaysian University Students / Mohd Noor Mamat - Mamat, Mohd Noor (Institute of Graduate Studies, UiTM, 2012)
Environmental crisis and ecological problems produced a global call to involve all residents of the Earth. Global warming, climate change, rise of the sea level, glacier decrease, food crisis, health hazards, deforestation and others are among the problems, affected by human attitude. For that, environmental attitude development becomes more serious as UNESCO declared that 2005- 2014 as ‘the decade of education for sustainable development’. Environmental attitude is best measured with affective outcomes; factual knowledge and behavior intention component to meet behavioral component. There is lack of study about the affective impacts of the environmental-related courses especially using a comprehensive instrument of environmental attitude. The objective of this research is to develop a valid and reliable Hadhari Environmental Attitude Test (HEAT) to assess the student’s environmental attitude after attending the environmental ethics course. Initial study has been done to support the development of the instrument, validated by the experts in education and environmental studies. HEAT comprises of 60 items on environmental attitude within ten dimensions, with reference to Quranic and prophetic values and in parallel with global and local’s concern.